Abdominopelvic actinomycosis mimicking disseminated peritoneal carcinomatosis. (21st November 2013) - Hildyard, Catherine A T; Gallacher, Neil J; Macklin, Philip S
Abstract : We present a case of a 38-year-old woman who presented with symptoms suggestive of intra-abdominal or pelvic malignancy: marked weight loss, abdominal pain, altered bowel habit, anorexia and fatigue. The findings of multiple peritoneal deposits, adnexal and presacral masses on CT imaging and appearances on diagnostic laparotomy also suggested malignancy. However, the histological analysis was inconsistent with malignancy and revealed an infection with Actinomyces israelii . The patient started a course of intravenous antibiotics and complete resolution is expected. An intrauterine contraceptive device was identified as the likely source of the infection.